2016
DOI: 10.1111/pbi.12650
|View full text |Cite
|
Sign up to set email alerts
|

Golden bananas in the field: elevated fruit pro‐vitamin A from the expression of a single banana transgene

Abstract: SummaryVitamin A deficiency remains one of the world's major public health problems despite food fortification and supplements strategies. Biofortification of staple crops with enhanced levels of pro‐vitamin A (PVA) offers a sustainable alternative strategy to both food fortification and supplementation. As a proof of concept, PVA‐biofortified transgenic Cavendish bananas were generated and field trialed in Australia with the aim of achieving a target level of 20 μg/g of dry weight (dw) β‐carotene equivalent (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
111
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 164 publications
(114 citation statements)
references
References 32 publications
0
111
0
3
Order By: Relevance
“…There remains, however, persistently high levels of VAD particularly in remote hard-to-reach areas that will only be addressed through more innovative strategies. As such, where bananas are a major component of the daily carbohydrate intake, their biofortification with pVACs has the potential to help address VAD and therefore has become a key focus of local and international research and collaboration (Buah, Mlalazi, Khanna, Dale, & Mortimer, 2016;Paul et al, 2017). By increasing the amount of essential nutrients in staple food crops, biofortification aims to target malnourished populations in a more economically viable and sustainable way.…”
Section: Agronomically and Culturally Accepted Eahb Cultivars In Eastmentioning
confidence: 99%
See 1 more Smart Citation
“…There remains, however, persistently high levels of VAD particularly in remote hard-to-reach areas that will only be addressed through more innovative strategies. As such, where bananas are a major component of the daily carbohydrate intake, their biofortification with pVACs has the potential to help address VAD and therefore has become a key focus of local and international research and collaboration (Buah, Mlalazi, Khanna, Dale, & Mortimer, 2016;Paul et al, 2017). By increasing the amount of essential nutrients in staple food crops, biofortification aims to target malnourished populations in a more economically viable and sustainable way.…”
Section: Agronomically and Culturally Accepted Eahb Cultivars In Eastmentioning
confidence: 99%
“…In contrast, the commercial Cavendish cultivar "Williams" has only 57 μg/100 g fw β-carotene (Englberger, Wills, et al, 2006). There is circumstantial evidence that both time of fruit development, and the prevailing environmental conditions plays a critical role in this pVAC variability (Paul et al, 2017). There is circumstantial evidence that both time of fruit development, and the prevailing environmental conditions plays a critical role in this pVAC variability (Paul et al, 2017).…”
Section: Agronomically and Culturally Accepted Eahb Cultivars In Eastmentioning
confidence: 99%
“…Increases of not only iron and zinc [88], but also folate [89,90] and pro-vitamin A in staple crops of the poor [42,49,91] are all extremely important for human health. All of them have been achieved using gmo-technology, where conventional breeding was not possible.…”
Section: Principlementioning
confidence: 99%
“…Transgenesis has also be used, with various levels of success so far, to introduce provitamin A traits into other important food security crops where (previously considered as) conventional plant breeding techniques could not be effective: cassava, sorghum and plantain (also called cooking banana) [5,91], all after Golden Rice's technology was published [42,49]. Professor Beyer's molecular pathway engineering expertise was sought by all these projects at one time or another.…”
Section: Principlementioning
confidence: 99%
“…To be compatible with organic farming, it seems to me essential that any transgene flow is excluded by restricting these manipulations to cisgenesis or genome editing approaches that do not introduce any foreign DNA, unless banana cultivars are used that are proven to be completely infertile. The authors' lab has shown, in a recent proof of concept [21] using the Cavendish cultivar, that a substantial increase in pro-vitamin A can be obtained by the integration of banana gene sequences exclusively. The data show that the use of a banana promoter as well as the banana phytoene synthase 2a gene results in bananas expressing a 10-fold higher level of pro-vitamin A which is reflected in the golden flesh, hence the name golden banana.…”
Section: The Banana Casementioning
confidence: 99%